2015
DOI: 10.4172/2157-7110.1000529
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Kinetics of Growth of Bacteriocin like Substance Produced by Lactic Acid Bacteria Isolated from Ewe Milk and Traditional Sour Buttermilk in Iran

Abstract: Ethnic people of Iran consume variety of traditional fermented milk products including buttermilk made from ewe's milk. The purpose of this study was to isolate and characterize bacteriocin producing by Lactic acid bacteria from these products, and to exploit their potential as bio preservative. Ten strains of Lactic acid bacteria isolated from ewe's milk, traditional yoghurt and sour buttermilk from different areas in Azarbayjan-e-sharqi, Iran were screened for their ability to produce bacteriocin like inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The addition of autochthonous LABs during cheesemaking can represent a good compromise between the safeguarding of traditional products, the adoption of solutions that allow high levels of food safety, and the possibility to maintain traditional manufacturing technologies [ 66 ]. In agreement with the results of other investigations [ 67 ], this study demonstrated a prevalence of Gram-positive bacteria in raw sheep milk, almost equally divided between rod-shaped bacilli (50.7%) and cocci (49.3%). Of these bacteria, 33.6% were identified as presumptive LABs due to their morphological and biochemical features, and 13/74 (17.6%) demonstrated antilisterial activity in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…The addition of autochthonous LABs during cheesemaking can represent a good compromise between the safeguarding of traditional products, the adoption of solutions that allow high levels of food safety, and the possibility to maintain traditional manufacturing technologies [ 66 ]. In agreement with the results of other investigations [ 67 ], this study demonstrated a prevalence of Gram-positive bacteria in raw sheep milk, almost equally divided between rod-shaped bacilli (50.7%) and cocci (49.3%). Of these bacteria, 33.6% were identified as presumptive LABs due to their morphological and biochemical features, and 13/74 (17.6%) demonstrated antilisterial activity in vitro.…”
Section: Discussionsupporting
confidence: 93%
“…Table ( 1) shows the susceptibility of lactic acid bacteria to grow at different temperatures (10, 37, 45) °C, the results showed that all the isolates under study could grow at a temperature of (37) °C, 42.8% of the isolates could grow at a temperature of (10) °C, and 50% of the isolates can grow at 45 degrees Celsius. These results are in agreement with the findings of [20], that the isolates belonging to lactic acid bacteria differed in their ability to grow at temperatures 10, 15, and 45, the results converged with what was found [21], mentioning that some strains of the genus Lactobacillus can grow at low and high temperatures less than 15 °C and some strains grow at temperatures up to 55 ° C. Heat IOP Publishing doi:10.1088/1755-1315/1158/11/112016 4 resistance of bacteria is affected by genetic factors, differences between species, physiological state of cells, and environmental factors such as pH, salt content, and preservatives [22].…”
Section: The Ability Of Lactic Acid Bacteria To Grow At Different Tem...supporting
confidence: 93%
“…Considering the results, the most frequent genus obtained were Lactococcus. Descriptions of L. lactis and E. faecalis in sheep milk have also been presented by Medina et al (2001), Delavenne et al (2012), Iranmanesh andEzzatpanah (2015), andKopčáková et al (2018).…”
Section: Identification Of Lactic Acid Bacteria By Mass Spectrometry mentioning
confidence: 93%
“…Despite the importance for the dairy industry, few studies have focused on autochthonous lactic microbiota in sheep milk. Most of the studies identified lactic acid bacteria (LAB) Enterococcus, Lactococcus, Lactobacillus and Leuconostoc as the most prevalent genera (CHANOS;WILLIAMS, 2011;IRANMANESH;EZZATPANAH, 2015). In general, the LAB constitute a heterogeneous group of Gram-positive bacteria, generally non-sporulating, characterized by bacilli or coccus morphology, catalase-negative, aerobic or facultatively anaerobic, acid-tolerant, and usually producing lactic acid as the major metabolic end-product of carbohydrate fermentation (CARR et al, 2002;LIU et al, 2011).…”
Section: Introductionmentioning
confidence: 99%